Problems in Li Ning’s Strategy and Countermeasures - Liu, Songling; Bi, Chuanchen (Technium Social Sciences Journal, 2022)
Opportunities and challenges flood in at the same time in the general context of the advance of the times and the ever-changing economic situation, especially in the era of sluggish economic recovery since the pandemic. Li Ning, a Chinese brand, stood up to upcoming dares and seized the moment, and has always been one step ahead of competitors. This paper, starting with the general environment faced by Li Ning, dissected progress made by the company in virtue of market segmentation, interpreted the basis for its strategic decision with SWOT analysis method, raised effective and feasible strategic decision-making, and offered the corresponding countermeasures to make up for its deficiencies, thereby availing its growth and enabling it to sustain current position among other local competitors.